2013
DOI: 10.1016/j.vaccine.2013.10.051
|View full text |Cite
|
Sign up to set email alerts
|

Increased efficacy of a trivalent nicotine vaccine compared to a dose-matched monovalent vaccine when formulated with alum

Abstract: Vaccination against nicotine is a potential treatment for tobacco smoking. Clinical trials show effect only in high antibody responders; therefore it is necessary to increase the effectiveness of nicotine vaccines. The use of a multivalent vaccine that activates several B cell populations is a possible approach to increase antibody response. The aim of this study was to investigate whether three different nicotine immunogens could be mixed to generate independent responses resulting in additive antibody titers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 36 publications
(27 reference statements)
2
35
0
Order By: Relevance
“…14.3A). The effects of bi- or trivalent nicotine vaccines on nicotine distribution in rats mirror the titers and are also additive (de Villiers, Cornish, Troska, Pravetoni, Pentel, 2013). An additional benefit seen in this study is that some animals with a low response to one immunogen had a high response to another, reducing the number of low or nonresponders.…”
Section: Strategies For Improving Vaccine Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…14.3A). The effects of bi- or trivalent nicotine vaccines on nicotine distribution in rats mirror the titers and are also additive (de Villiers, Cornish, Troska, Pravetoni, Pentel, 2013). An additional benefit seen in this study is that some animals with a low response to one immunogen had a high response to another, reducing the number of low or nonresponders.…”
Section: Strategies For Improving Vaccine Efficacymentioning
confidence: 99%
“…(A) Trivalent nicotine vaccine (de Villiers et al, 2013). Rats were vaccinated with three structurally distinct nicotine immunogens (linkers attached at different positions, carrier proteins; rEPA, recombinant exoprotein A; KLH, keyhole limpet hemocyanin; malKLH, maleimide activated KLH) or a dose-matched monovalent immunogen s.c. with alum adjuvant.…”
Section: Figure 141mentioning
confidence: 99%
“…In rats, combining 3 nicotine immunogens based on haptens with linkers at the 1′ or 3′ position of the pyrrolidine ring, or 6 position of the pyridine ring, produced additive antibody titers and greater ability to prevent nicotine distribution to brain than a monovalent vaccine (de Villiers et al, 2013). In addition, some rats with poor responses to one immunogen had brisk responses to one of the others.…”
Section: Vaccines For the Treatment Of Tobacco Addictionmentioning
confidence: 99%
“…To increase efficacy, support has been given to the use of multivalent vaccines, i.e. combination of multiple vaccine products and concurrent use with other smoking cessation pharmacotherapy [152]. Animal studies have shown a strong synergistic effect of a nicotine vaccine in combination with the nAChR antagonist mecamylamine [153].…”
Section: Nicotine Vaccinesmentioning
confidence: 99%